Pengaruh Kemampuan Tata Bahasa dan Kosa Kata terhadap Penguasaan Menulis Paragraf Narasi pada Siswa Kelas X SMAN Negeri 10 Kota Jambi - Elviza Elviza (Jurnal Ilmiah Dikdaya, 2021)
This study to know determine the effect of grammar skills on mastery of writing narrative paragraphs. This is to determine the effect of vocabulary skills on writing mastery of narrative paragraphs and to determine the effect of grammar and vocabulary skills on writing mastery of narrative paragraphs. The population and sample in this study were students of class X majoring in science and social studies at SMA Negeri 10 Jambi City, totaling 245 people. Based on the results of the research above, it was obtained that as many as 75 (30.61%) students had a high level of vocabulary mastery, 103 students (42.04%) had a moderate level of vocabulary mastery, and as many as 67 students (27.34%) had a mastery level. low. Based on the results of the study, vocabulary mastery was as many as 40 students or 16.32%, students who had a moderate level of vocabulary mastery were 145 students (59.18%) and vocabulary mastery of students who were in the low category were 60 students (24.48%). ). Based on the results of the study, vocabulary mastery was as many as 40 students or 16.32%, students who had a moderate level of vocabulary mastery were 145 students (59.18%) and vocabulary mastery of students who were in the low category were 60 students (24.48%).